Papers - Smelting - Reverberatory Smelting Practice - Forms of Copper Found in Reverberatory Slags (With Discussion) - Royal B. Jackman; Carle R. Hayward (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1934)
Two comprehensive papers have appeared regarding the forms of copper that occur in smelter slags, one by Frank E. Lathe1 and the other by C. G. Maier and G. D. Van Arsdale.2 These authors comment on other published results and draw conclusions from their own investigations. The development of X-ray examination of minerals and improvement in high-power microscopic methods make it possible today to get additional evidence by means that were not available to earlier investigators. The present work was confined to reverberatory slags obtained from five different plants. Some definite conclusions were reached regarding the forms of copper present in these slags. In most cases these agree with some of the findings of Maier and Van Arsdale but new methods of attack were used in the investigation. Conclusions of Previous Investigators Various important conclusions reached by previous investigators are summarized in the following paragraphs, arranged chronologically. William A. Heywood:3 Slag losses increase with grade of matte but with the same grade of matte losses decrease as the acidity of the slag increases. Lewis T. Wright:' Slag losses are only partly due to prills of matte. It is suggested that part of the copper is dissolved in the slag. J. Parke Channing9 A considerable part of the copper enters the slag as silicate or oxide and not as sulfide. C. A. Grabill:6 Slag losses are both physical and chemical. Physical losses, due to poor settling, gas flotation and slight differences in specific gravity, are small under normal conditions. Chemical losses may- be due to formation of oxides or to solution of metals and sulfides. The last is considered the most important. John W. James:' The copper in converter slag is largely the oxide and as such enters the reverberatory slag when converter slag is added to the charge.